Identifying learning strategies among first-year engineering students - Arthur James Swart; Marietjie Havenga (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
The Williamson’s self-rating scale for self-directed learning (SRSSL) questionnaire is applied to determine which learning strategies first-year African engineering students have adopted at the start of a problem-based learning module that is designed to promote self-directed learning (SDL). This approach can help academics to better identify “who” their students are, thereby helping them to leverage and improve on current learning strategies to try and enhance student engagement. A requirement for becoming a great teacher in one’s field of study is to come to know your students cognitively, affectively, and culturally. Many different cultures have strongly embedded identities that would form and shape student learning strategies. Intended outcomes: The purpose of this article is to identify what self-perceived learning strategies engineering students have adopted from their school education, by using a standardized questionnaire. Student perceptions regarding their own levels of SDL, as well as their expectations and actual achievements of academic success, are also presented. The purpose of the problem-based learning module that is used in this study is to give engineering students the opportunity to develop managerial skills as the module involves much teamwork, where imaginary companies are formed with the goal of designing and constructing specific projects for real industry-based clients. A time-lag study is used where quantitative data are collected using a standardized questionnaire. Results indicate that 77% of females report high levels of SDL, while only 66% of males do so. No significant correlation exists between the self-reported scores of the students and their final grades. However, the three most reported learning strategies include interactive teaching and learning sessions, simulations, and educational interactive technologies. It is recommended that academics encourage SDL among first-year engineering students by helping them to identify appropriate learning strategies that can help them to enhance their engagement with the course and subsequent academic success.